Беспроводная сеть zigbee для сбора данных с ethernet шлюзом - Губарев, А. А. (ХНУРЕ, 2012)
The purpose of this work is to develop a complex for the implementation of wireless sensor networks for information gathering, processing and transmission over the Internet or intranet.
Keywords: ethernet шлюз; беспроводная сеть zigbee